Mechanism of Fragility at BCL2 Gene Minor Breakpoint Cluster Region during t(14;18) Chromosomal Translocation - Nambiar, Mridula (American Society for Biochemistry and Molecular Biology, 2012)
The t(14;18) translocation in follicular lymphoma is one of the most common chromosomal translocations. Breaks in chromosome 18 are localized at the 3′-UTR of BCL2 gene or downstream and are mainly clustered in either the major breakpoint region or the minor breakpoint cluster region (mcr). The recombination activating gene (RAG) complex induces breaks at IgH locus of chromosome 14, whereas the mechanism of fragility at BCL2 mcr remains unclear. Here, for the first time, we show that RAGs can nick mcr; however, the mechanism is unique. Three independent nicks of equal efficiency are generated, when both Mg(2+) and Mn(2+) are present, unlike a single nick during V(D)J recombination. Further, we demonstrate that RAG binding and nicking at the mcr are independent of nonamer, whereas a CCACCTCT motif plays a critical role in its fragility, as shown by sequential mutagenesis. More importantly, we recapitulate the BCL2 mcr translocation and find that mcr can undergo synapsis with a standard recombination signal sequence within the cells, in a RAG-dependent manner. Further, mutation to the CCACCTCT motif abolishes recombination within the cells, indicating its vital role. Hence, our data suggest a novel, physiologically relevant, nonamer-independent mechanism of RAG nicking at mcr, which may be important for generation of chromosomal translocations in humans.